Dose-remission of pulsating electromagnetic fields as augmentation in therapy-resistant depression: a randomized, double-blind controlled study. Issue 5 (10th April 2014) - Straasø, Birgit; Lauritzen, Lise; Lunde, Marianne; Vinberg, Maj; Lindberg, Lone; Larsen, Erik Roj; Dissing, Steen; Bech, Per
<x content-type="archive" xml:space="preserve">Abstract</x> Objective To evaluate to what extent a twice daily dose of Transcranial Pulsating ElectroMagnetic Fields (T-PEMF) was superior to once daily in patients with treatment-resistant depression as to obtaining symptom remission after 8 weeks of augmentation therapy. Methods A self-treatment set-up of the T-PEMF device was used allowing self-administration by patients in own homes. All patients were treated for 30 min per T-PEMF session. The antidepressant medication the patients were receiving at baseline remained unchanged during the trial. The patients were randomised to either one T-PEMF dose (active dose in the morning and sham in the afternoon) or two T-PEMF doses (active dose both morning and afternoon) in a double-blind procedure. A score of 7 or less on the Hamilton Depression Scale (HAM-D17) was the criterion of remission. Results In total 34 patients received active T-PEMF once a day and 31 patients twice daily. After 5 weeks of therapy remission was obtained in 26.5% and 32.3% on one dose and two doses of T-PEMF, respectively. After 8 weeks the rate of remission was 73.5% and 67.7%, respectively. The side effects as measured by the Udvalget for Kliniske Undersøgelser scale showed a better toleration of the antidepresssive medication in both treatment groups, which was reflected by the WHO-5 well-being scale with increased scores in both groups of patients. Conclusion The high remission rate obtained by the T-PEMF augmentation was not a dose effect (one versus two daily T-PEMF sessions) but was explained by the extension of the treatment period from 5 to 8 weeks.